2011
DOI: 10.3341/kjo.2011.25.6.375
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Intraocular Lens Power Calculation Formulas in Primary Angle Closure Glaucoma

Abstract: PurposeTo compare the accuracy of intraocular lens (IOL) power calculation formulas in eyes with primary angle closure glaucoma (ACG).MethodsThis retrospective study compared the refractive outcomes of 63 eyes with primary ACG with the results of 93 eyes with normal open angles undergoing uneventful cataract surgery. Anterior segment biometry including anterior chamber depth, axial length, and anterior chamber depth to axial length ratio were compared by the IOL Master. Third generation formulas (Hoffer Q and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 22 publications
(24 reference statements)
3
21
1
Order By: Relevance
“…In a comparison the formulas of IOLMaster, Hoffer Q produced the least prediction error. This finding is consistent with a previous study using the IOLMaster formulas, which showed the Hoffer Q formula to induce better results than the SRK/T formula in angle‐closure glaucoma eyes . The Haigis formula produced the most hyperopic results in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In a comparison the formulas of IOLMaster, Hoffer Q produced the least prediction error. This finding is consistent with a previous study using the IOLMaster formulas, which showed the Hoffer Q formula to induce better results than the SRK/T formula in angle‐closure glaucoma eyes . The Haigis formula produced the most hyperopic results in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Its inaccuracy might be caused by ACD biometric data. An increase of 1 mm ACD will cause a change in the postoperative refraction in the Haigis formula of 0.5 to 0.6 diopter . Increase in ACD was much higher in the patients with narrow angle so that ACD constant from based on normal eyes can cause a change in postoperative refraction.…”
Section: Discussionmentioning
confidence: 96%
“…The refractive accuracy is, however, less than that reported in an analysis of 17 056 eyes undergoing cataract surgery in Sweden, where 71% were within ±0.5D and 93% within ±1.0D 13. The EAGLE results compare favourably with the previous studies of refractive outcomes in patients with PACG where 49%–68% eyes (depending on the IOL power formula used) were reported to be within ±0.5D target in a study of 63 eyes14 and 77% eyes within 1.0D target refraction in a study of 49 eyes with PACG 15…”
Section: Discussionsupporting
confidence: 44%
“…The biometric variables that are used for intraocular lens (IOL) calculation depend on the chosen IOL formula. Current thirdgeneration and fourth-generation IOL power calculation formulas require the basic variables of axial length (AL), anterior chamber depth (ACD), keratometry (K), and corneal diameter (CD) values [1][2][3]. The IOL power calculation formulas achieve precise results in eyes with ALs between 22.0 and 25.0 mm.…”
Section: Introductionmentioning
confidence: 99%